Structural and electronic properties of chemically functionalized SnC monolayer: a first principles study. (9th December 2019) - Hoat, D M; Naseri, Mosayeb; Ponce-Péreze, R; Hieu, Nguyen N; Rivas-Silva, J F; Vu, Tuan V; Tong, Hien D; Cocoletzi, Gregorio H
Abstract: We investigate the chemical functionalization effect on the structural and electronic properties of SnC monolayer using first-principles calculations. Specifically, the chlorinated-, fluorinated- and Janus-functionalized monolayers are considered. Based on our calculations, the pristine SnC monolayer is dynamically stable with a planar structure. Its electronic band gap calculated with the HSE06 hybrid functional is 2.371 eV. The inclusion of halogen atoms (F and Cl) destroys the planarity and transforms the hybridization from sp 2 to sp 3 . The half-halogenation induces the metallization of the SnC monolayer, while the indirect-to-direct band gap transition can be reached by means of the full-halogenation and Janus-functionalization. Results show that the pristine SnC monolayer electronic structure can be effectively modulated by the chemical functionalization. Therefore, we hope that results presented herein can be of good reference for the SnC monolayer practical applications as well as other 2D materials.